2013
DOI: 10.1051/0004-6361/201322137
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of coronal features to understand the solar EUV and UV irradiance variability

Abstract: Context. The study of solar irradiance variability is of great importance in heliophysics, the Earth's climate, and space weather applications. These studies require careful identifying, tracking and monitoring of active regions (ARs), coronal holes (CHs), and the quiet Sun (QS). Aims. We studied the variability of solar irradiance for a period of two years (January 2011-December 2012) using the Large Yield Radiometer (LYRA), the Sun Watcher using APS and image Processing (SWAP) on board PROBA2, and the Atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In our previous paper, Kumara et al (2014), we described the details of all the instruments, calibration of data, degradation of instruments, and the SPoCA. We also explained the observational details and procedure applied to segment the coronal features (ARs/CHs/QS/FD) for the period January 2011 to December 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous paper, Kumara et al (2014), we described the details of all the instruments, calibration of data, degradation of instruments, and the SPoCA. We also explained the observational details and procedure applied to segment the coronal features (ARs/CHs/QS/FD) for the period January 2011 to December 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Our objective in this study is the practical conversion of solar intensity and magnetic field images into physically interpretable quantities describing the solar magnetic cycle and its consequences on the radiative output of the Sun. We have used the Spatial Possibilistic Clustering Algorithm (SPoCA; Barra et al 2008Barra et al , 2009Verbeeck et al 2014;Kumara et al 2014), which is an image segmentation algorithm that allows the separation of solar intensity images and magnetograms into three characteristic structures on the Sun: active regions (ARs), coronal holes (CHs), and quiet sun (QS) (Kumara et al 2014). Understanding the EUV and UV irradiance variability from spatially resolved intensity and magnetic field observations is an important issue in space weather and climate applications.…”
Section: Introductionmentioning
confidence: 99%
“…The boundaries of networks coincide with the boundaries of large convective cells seen in Dopplar-grams (Leighton 1959;Leighton et al 1962) and the contribution to the solar irradiance due to networks vary by few percent with the solar cycle phase (Worden et al 1998). Quiet Sun (QS) identified by Kumara et al (2014) represents solar corona and is the greatest contributor to solar irradiance with up to 63% in the EUV spectral irradiance in terms of intensity. The active regions contribute by about 10% and off-limb features about 24%.…”
Section: Summary and Discussionmentioning
confidence: 76%
“…Kariyappa and Pap (1996) reported that the variation in spatial index and full width half maximum (FWHM) of the intensity distribution of the chromospheric features such as plages and networks as observed from Ca-K spectroheliograms representing the activity agrees with the UV irradiance measured in MgII h and K lines. Further, Verbeeck et al (2014) and Kumara et al (2014) used segmentation method to identify the active regions, coronal holes and Quiescent Sun (QS) to study the UV and EUV variability of the Sun. Identified active regions are likely to have resemblance with Ca-K plages.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation